Grid computing e cloud computing: análise dos impactos sociais, ambientais e econômicos da colaboração por meio do compartilhamento de recursos computacionais - Silva, Diogo Cortiz da (2009)
This research debates the excess of worldwide available computational resources with exceeded processing capacity and also how the utilization of the sharing and collaboration concepts influence the integration of those devices to constitute an economic environment with high processing capacity. Currently, it is possible to find a great amount of personal computers, servers and others devices that show high level of idleness, while they could be being used for another purpose, once there are many scientific researches, collaborative projects and digital inclusion programs that are short of resources to reach theirs objectives. The Grid Computing technology was conceived as an alternative to integrate geographically distributed resources pertaining to different domains, enabling a decentralized computational environment. The main objective of this research is to analyze how this technology can generate benefits to the social, environment and economic contexts. In the social approach, Grid Computing stimulates the collaboration and the sharing of computational resources and applications, as well as providing features that are very useful for data transparency between many domains. Those characteristics are also important for the scientific inclusion. The first Case Study approaches the importance of Grid Computing for the collaborative tasks found in the scientific project of the Large Hadron Collider (LHC), which allowed many research institutions and universities around the world to build a shared computational environment of large scale for processing the data generated by LHC. In the environment context, this technology also presents some characteristics to make the computational resources more energy efficient increasing the use of its computational capacities. The second Case Study analyzes the data related to the amount of personal computers connected in the Internet and how to implement Grid Computing based on the Volunteer Computing model to make those computers more productive with no relevant impact in the energy consumption. This research also highlights the synergy between Grid Computing and Cloud Computing, its financial advantages and the generation of new business models based on the commercialization of platform and software as a service in the Internet. The third Case Study analyzes a Cloud Computing model that delivers computational resources (such as a whole server) as a service, enabling a scenario where companies and people could contract a computational environment with a quick provisioning with no need to purchase equipments and to invest in implementation projects. Finally, it is possible to appoint both technologies as relevant trends for the coming years, which can be an influence to generate new software models, platforms and services focused in the Internet